Penerapan Terapi Orientasi Realita pada Pasien Waham Kebesaran : Studi Kasus - Asmi Zaelani, Faisal; Saryomo, Saryomo (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Mental health is a state of physical, mental, and social well-being that enables individuals to function optimally. Mental disorders such as schizophrenia can lead to distortions of reality, one of which is delusion, defined as a belief that is not consistent with reality but is strongly maintained. Delusions can disrupt thought processes, emotions, and behavior, thus requiring appropriate management. One of the nursing interventions that can be applied is reality orientation therapy. This study aims to describe the implementation of nursing care in a patient with a thought process disorder: grandiose delusion. This study used a case study design involving one patient with schizophrenia who had a nursing diagnosis of grandiose delusion, conducted over three days. The results showed that the implementation of the Implementation Strategy (SP) through reality orientation therapy improved the patient’s ability to orient to person, place, and time, and gradually reduced the intensity of delusional symptoms. The conclusion indicates that reality orientation therapy is effective as a nursing intervention in managing patients with grandiose delusions